Chemical Composition and Antibacterial Activity of Essential Oil of Skimmia lauriola from Tehri Garhwal - Naveen Kumar; Kiran Bharti; J. S. Jangwan; Shyam Vir Singh (Challenges and Advances in Chemical Science Vol. 3, 2021)
Aromatic plants have played key roles in the lives of tribal peoples living in the Himalaya by providing products for both food and medicine. The chemical composition of the essential oils of Skimmia lauriola (leaves) growing in Northern Garhwal, Himalaya has been studied. The wildly growing plants were collected from Dhanolti region of Tehri Garhwal. The essential oil was extracted using hydro distillation techniques and analysed using GC/MS. Thirty seven components were identified, accounting for 86.33% of the total oil. The oil is mainly composed of linalool acetate (26.40 %), L-linalool (14.18 %), \(β\)-phellendrene (9.03 %), prejeijerene (7.06 %), \(α\)-terpineol (6.25%), geranyl acetate (3.89 %) and myrcene (2.18 %). Antibacterial activity of the essential oil was evaluated. Pseudomonas aurens had the most activity, with an 8 mm zone of inhibition, followed by Escherichia coli with a 5 mm zone of inhibition, while Bacillus subtilis and Staphylococcus aureginosa were completely unaffected.